Patient safety in an obstetric unit: The perception of the nursing team (Research, Society and Development, 2023)
Introduction: complications can have a negative impact on patient care and safety during pregnancy, with maternal mortality being a sign of health neglect and the main indicator for evaluating the quality of care for women during labor and birth. Patient safety is a pillar supporting the quality of care and, considering the perinatal paradox experienced today, in which technological advances have failed to improve maternal and neonatal mortality indicators, it is important to analyze patient safety in obstetric care. Objective: to understand the actions and perception of the nursing team that works in an Obstetric Inpatient Unit regarding patient safety. Methodology: this is an exploratory research with a qualitative approach, developed with professionals from the nursing team of an Obstetric Inpatient Unit located in a municipality in the Northwest Region of the State of Rio Grande do Sul. Results: the following categories were identified: Team perception regarding Patient Safety; Patient Safety and obstetrics and; Importance of adhering to Patient Safety protocols and training in the Hospital Institution. Final considerations: the research results demonstrate that patient safety is in a regular condition, with many discordant answers to some interview questions, which show that professionals do not have unanimous and in-depth knowledge on the subject of patient safety, just as it was possible to identify that in the investigated institution there are no protocols for specific care for pregnant women and there are only nursing routines.